Urbanization and Its Effects on Social Relationships - Sahare, Ravindra (AG Volumes, 2025)
Given the ongoing rise in urbanisation, it is crucial to comprehend how social structure, urbanisation, and environmental sustainability interact in order to promote sustainable urban development. The impact of urbanisation on social relationships is the subject of this article. This review reveals that rapid urbanization, driven by population growth, improved infrastructure, and economic opportunities, significantly alters social relationships. Urban life fosters individualism, reduced household size, and weakened community ties due to congestion, privacy needs, and lifestyle changes. While urban areas offer improved services, they also face challenges like crime, pollution, and social fragmentation. Urbanization affects social cohesion through shifts in employment, environmental conditions, and cultural dynamics. Technology, though beneficial, may hinder meaningful social interactions if overused. Inclusive planning, community engagement, and sustainable development strategies are essential to mitigate negative impacts and strengthen social bonds in rapidly urbanizing societies.